A COMPREHENSIVE STUDY OF UTTAR-TANTRA IN SUSHRUTA SAMHITA - Chaudhari, Prof. Dr. Maheshkumar (International Journal of Ayurveda and Pharma Research, 2020)
Sushrut Samhita Uttartantra is dealt with many important topics. Main surgical part is described in detail in Sushrut Samhita 1st part. Remaining all like Ophthalmology, ENT, gynaecology and Obstetrics, Paediatrics, Agadtantra, Tantrayukti, etc, are illustrated in detail in Uttar-Tantra.The thoughts of Sushruta of those days are observing true even today. The surgery regarding Cataract, he described, is followed by today’s Ophthalmic surgeon as he illustrated in Uttartantra 4000 years back. Also Sushruta described about how the life should be ideally live in the form of Dincharya, Ratricharya, Rutucharya, etc, and specific time of consuming of medicine for instant cure of diseases, are the unique and unparallel specialty of Uttartantra of Sushruta Samhita. Perfect time of taking food and water, quantity of taking food and water are also dealt with this topic very smoothly. Concept of Agni and applicability of seasonal regimen in the non-monsoon countries is another precious point of pride of Uttar-Tanra of Sushruta Samhita.Tantrayukti- is as a key to open the secrecy of meaning of the Sushruta Samhita. Tantrayukti makes easy to understand or digest the exact meaning of the Sushruta Samhita.